Ketahanan Membran Komposit Khitosan/ Polisulfon Terhadap pH - Haryati, Sri; Erna, Maria (Sainstek, 2008)
It has been done the resistance test of chitosan/polysulfon composite membrane toward of solvent. Result showed that composite membrane was resisted to pH of 5.5. It was indicated by the highest swelling percentage, that is 75.48%. These result were supported by porous photo membrane using SEM that is across-section , up surface and bottom photo showed that happed change porous structure membrane but structure tying membrane can not experiencing of damage. Keyword : composite membrane, chitosan,swelling percentage